Dual-Channel Pricing of Online Retail Based on Evolutionary Game Theory and Coevolutionary Algorithm. (28th April 2022) - Song, Yejiao; Ji, Chengjun
Abstract : For the offline market entry strategy and product pricing of online retailers in the retailer competitive supply chain structure, a supply chain game model composed of a single manufacturer, a single traditional retailer, and a single online retailer is constructed and an improved coevolutionary game algorithm (ICGA) is proposed to solve the model. In addition, a dynamic optimization model based on dissatisfaction is established to dynamically adjust the coevolutionary game algorithm. The research shows that when online retailers open offline channels, with the increase of offline market share of online retailers, the profits of traditional retailers decrease and manufacturers increase, while the profits of online retailers increase first and then decrease; there is a maximum point. The profits of online retailers, manufacturers, and supply chains will be optimized due to the opening of offline channels. When the offline market share of online retailers is lower than a specific threshold, the new offline channels of online retailers will also make the profits of traditional retailers greater. At this time, the profits of all members of the supply chain will be optimized. Finally, the final optimization stability strategy can make the offline retail and online retail achieve the best operation state, and the overall theoretical rate of supply chain has been significantly improved, which proves the effectiveness and superiority of the proposed model and algorithm.